Mechanisms involved in the increase of borosilicate glass alteration by interaction with the Callovian-Oxfordian clayey fraction. (November 2018) - Debure, Mathieu; De Windt, Laurent; Frugier, Pierre; Gin, Stéphane
Abstract: The influence of clay minerals of the Callovian-Oxfordian claystone on the alteration of international simple glass (ISG) was investigated through batch experiments conducted at 90 °C and via geochemical modeling. Several clay/glass weight ratios ranging from 0.9 to 91 were tested. These experiments revealed that the mechanisms controlling glass alteration were indirectly dependent on that ratio. The solution and solid characterizations indicated the presence of non-clay minerals such as pyrite, Mg-calcite, quartz, dolomite, and magnesite in the treated clay material, which influenced the results. The clay minerals were poorly reactive. The carbonates and clay exchanger released reactive magnesium in solution. Furthermore, it is worth noting that the reactors did not prevent air-solution interactions. The simulations demonstrated that O2 contribution needs to be considered to explain the clay-glass interactions. The mechanisms controlling clay-glass interactions were deciphered based on mineralogical characterizations and geochemical modeling. At high clay/glass ratio, glass dissolution was sustained by pyrite oxidation and possibly iron silicate precipitation, while at low clay/glass ratio the passivation of the glass was prevented by the precipitation of magnesium silicate minerals. Highlights: The reactivity of the clay in contact of the glass was low. Mg and Fe formed secondary phases with Si that enhanced the glass alteration. Mg came from Mg-carbonates and exchanger and Fe came from pyrite. Glass model called GRAAL was implemented in PhreeqC. The modeling coupled successfully the glass and clay models, developed separately.